Návrh komunikační strategie společnosti - Rolínová, Lenka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Cílem mojí diplomové práce na téma „Návrh komunikační strategie společnosti“ je navržení komunikační strategie pro společnost Poex, a.s. Práce je rozdělena na tři hlavní části. V první části jsou popsána teoretická východiska. Druhá část se zabývá analýzou současné situace firmy a jejího okolí. Třetí část je návrhová, kde jsou na základě teoretických poznatků a zpracovaných analýz, uvedeny návrhy na efektivní komunikační strategii a návrhy na odstranění slabých stránek firmy.

The main taim of this thesis called „Design of communication strategy of a company“ is a suggestion of communication strategy for the company Poex, a.s. The thesis is divided into three main parts. The first part of the thesis contains a description of theoretical resources and fundamental knowledge. The sekond part of the thesis is focused on analysis of the current situation in of the company and its significant environment. The third part is a design which is based on theoretical findings and processed analyses. In the final part are presented proposals for an effective communication strategy and potential suggestions for improvement of the company weaknesses.
Design of Communication Strategy of a Company
Keywords: Marketingová komunikace; komunikační strategie; komunikační mix; reklama; propagace; Marketing communication; communication strategy; communication mix; advertising; promotion